Role of Sheikh Okutagidi Towards the Spread of Islam in Ilorin Emirate, North-Central Nigeria (1931-2016) - Ridwan, Idris Tosho; Abdulganiyu, Jawondo Ibrahim; Ishola, Jimba Abdulhameed (International Journal of Islamic Educational Psychology, 2022)
Ilorin is blessed with many Islamic scholars engaged in da'wah activities, earning the town the proverbial title of Ilu Alfa (the seat of erudite Muslim scholars). Islamic scholars face significant challenges in adhering to Islamic principles and religious proselytization. Sheikh Alfanla Okutagidi's da'wah activities in Ilorin were noticeable in Islamic propagation in Ilorin Emirate. The study aims to examine the role of Sheikh Alfanla Okutagidi in spreading Islam in the Ilorin Emirate, Kwara State, North-Central Nigeria. A qualitative methodology was adopted to achieve this objective, which relied on primary and secondary sources, including observation, oral interviews, and literature. The study revealed that he started Islamic propagation using the Qur'an and hadith to pass the message of Islam. He was strictly against western education. To keep Islam in the entire Ilorin Emirate, he waged war against paganists, foodstuff sellers, and alcohol sellers. Therefore, Sheikh Alfanla Okutagidi made significant contributions to the growth and, to a large extent, eradication of paganism in the Ilorin Emirate with fanaticism. Thus, fanaticism and radicality should be omitted from the da'wah activities since Islam has no compulsion, so it will not threaten the community's peace.